Dewey decimated : a haunted library mystery - Brook, Allison (Brook, Allison. Haunted library mystery, 2022)
"Carrie Singleton is just off a hot string of murder cases centered around the spooky local library in Clover Ridge, Connecticut. She could really use a break -- -but no such luck, as she; Smokey Joe, the resident cat; and Evelyn, the library's ghost, are drawn into another tantalizing whodunit. First, a dead body is found in the basement of the building attached to the library, and it turns out to be Carrie's fianč's Uncle Alec, who Dylan hasn't seen in years. But Alec has no intention of truly checking out, and his ghost makes itself at home in the library, greatly upsetting the patrons. Carrie and Evelyn work hard to keep Alec out of sight, but what was he doing in Clover Ridge to begin with? And why was he killed? Meanwhile, the town council, of which Carrie is also a member, is embroiled in a hot-headed debate over the fate of the Seabrook Preserve, a lovely and valuable piece of property that runs along Long Island Sound. Turn it into an upscale park? Sell it to a condo developer? Or keep it as protected land? As the dispute rages, there's another murder, this time involving a council member. Could the two murders be connected? And could Carrie be next on the hit list?" --